2019
DOI: 10.1242/bio.043653
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide mitigates NLRP3 inflammasome-mediated inflammation through promoting autophagy via AMPK-mTOR pathway

Abstract: The aim of this study was to investigate whether exogenous hydrogen sulfide (H 2 S) could mitigate NLRP3 inflammasome-mediated inflammation through promoting autophagy via the AMPK-mTOR pathway in L02 cells. L02 cells were stimulated with different concentrations of oleic acid (OA), then cell viability and the protein expression of NLRP3 and pro-caspase-1 were detected by MTT and western blot, respectively, to determine appropriate OA concentration in this study. The cells were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
(52 reference statements)
2
27
0
Order By: Relevance
“…Targeting the effect of autophagy on NLRP3 with oral small molecule compound BBR might improve insulin resistance. Similar to the above results, our previous studies have shown that enhancing autophagy by hydrogen sulfide (H 2 S) suppresses NLRP3 inflammasome through AMPK-mTOR pathway in L02 cells induced by oleic acid ( Wang et al, 2019 ). AMPK-mTOR pathway is an important signaling pathway for the interaction between autophagy and NLRP3 inflammasome.…”
Section: The Interplay Between Autophagy and Nlrp3 Inflammasome In Glsupporting
confidence: 86%
“…Targeting the effect of autophagy on NLRP3 with oral small molecule compound BBR might improve insulin resistance. Similar to the above results, our previous studies have shown that enhancing autophagy by hydrogen sulfide (H 2 S) suppresses NLRP3 inflammasome through AMPK-mTOR pathway in L02 cells induced by oleic acid ( Wang et al, 2019 ). AMPK-mTOR pathway is an important signaling pathway for the interaction between autophagy and NLRP3 inflammasome.…”
Section: The Interplay Between Autophagy and Nlrp3 Inflammasome In Glsupporting
confidence: 86%
“…3-MA, an autophagy inhibitor, could counteract the effect of H2S, suggesting that autophagy mediated the effect of H 2 S on NLRP3 inflammasome-mediated inflammation. In addition, compound C, an AMPK inhibitor, could inhibit autophagy and counteract the anti-inflammatory effect of exogenous H 2 S. In summary, exogenous H 2 S inhibited NLRP3 inflammasome-mediated inflammation of hepatocytes through promoting autophagy via AMPK/mTOR pathway (Figure 4) [41,42]. Through consulting a large number of related literatures, we found that exogenous H2S could inhibit endoplasmic reticulum stress (ERS) in many diseases [28], and there was interaction between ERS and NLRP3 inflammasome [43], so whether exogenous H 2 S can inhibit NLRP3 inflammasome-mediated inflammatory response through ERS needs further study.…”
Section: H 2 S Plays Liver Protection Roles By Influencing Nlrp3 Inflammasomementioning
confidence: 98%
“…A chronic, low-level state of systemic and sterile inflammation is an important feature of DCM (Sharma et al, 2018 ). The NLRP3 inflammasome is an important complex protein that mediates inflammation (Wang H. et al, 2019 ). Studies showed that suppressing NLRP3 notably improved DCM (Ye et al, 2017 ).…”
Section: The Role Of H 2 S In Dcmmentioning
confidence: 99%